Gastric tonometry: effect of sucralfate on calculated intramural pH - Motsch, Johann; Bach, Alfons; Böhrer, Hubert; Schmidt, Heinfried; Schönau, Th.; Martin, Eike (Acta anaesthesiologica Scandinavica, 1995)
Tonometric measurement of gastric intramural pH (pHi) is a noninvasive method to assess adequacy of splanchnic perfusion. Calculation of pHi may be influenced by various factors. This prospective study was designed to determine if stress ulcer prophylaxis with sucralfate interferes with pHi measurement. Twenty-five adult patients admitted to the intensive care unit (ICU) after open heart surgery were studied. Nasogastric tonometers were placed. Patients received sucralfate 1 g via the nasogastric tube 8 hours after termination of surgery, thereafter every 6 hrs. Gastric luminal pH and intramural pH were determined immediately prior and 1 hour after the first sucralfate administration. Gastric intramural pH was calculated from the arterial HCO3 concentration and the tonometrically determined intraluminal PCO2 value using the Henderson-Hasselbaich equation. Intraluminal PCO2(SS) was measured to be 6.86±0.75 kPa prior to sucralfate administration as compared to 6.96±0.68 kPa 1 hour after 1 g sucralfate (P=0.92). Intramural pH, as calculated by tonometry, was 7.31±0.05 vs 7.31±0.05, and was thus not influenced by sucralfate administration (P=0.97). Mean gastric intraluminal juice pH was 4.2±1.3 compared to 4.2±1.2 (P=0.59). These data suggest that sucralfate does not interfere with tonometrically determined intraluminal PCO2 measurement and calculation of gastric intramural pH.
Gesehen am 21.11.2023